2006
DOI: 10.1021/es052593p
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Hormone Profiles of Urban and Tidal Rivers Using LC/MS/MS Equipped with Electrospray Ionization and Atmospheric Pressure Photoionization Sources

Abstract: A highly sensitive and uncomplicated method of analyzing steroidal hormones in river and estuarine water samples was developed using a liquid chromatography tandem mass spectrometer equipped with an electrospray ionization (ESI) source and atmospheric pressure photoionization (APPI) source. Steroidal hormones included not only estrogen but also androgen and conjugates of these two. APPI displayed greater sensitivity than ESI for most of the unconjugated steroids examined, with very high sensitivity for testost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
72
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 42 publications
5
72
0
1
Order By: Relevance
“…Alternative methods include the implementation of highperformance liquid chromatography MS (LC-MS) methodology where derivatization is often not needed. Recent examples reported in the literature include the analysis of androgens in waste water and surface water samples [8,9]. Although LC-MS(-MS) has been viewed as a potential method for analyzing a broad range of these compounds, matrix interference has been proven to cause potential problems.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative methods include the implementation of highperformance liquid chromatography MS (LC-MS) methodology where derivatization is often not needed. Recent examples reported in the literature include the analysis of androgens in waste water and surface water samples [8,9]. Although LC-MS(-MS) has been viewed as a potential method for analyzing a broad range of these compounds, matrix interference has been proven to cause potential problems.…”
Section: Introductionmentioning
confidence: 99%
“…Steroid hormones have been frequently detected in various environmental matrices, including soil, groundwater, surface water and sediments (Ying et al, 2002). These substances were often found at nanograms to micrograms per liter concentrations in surface water (Ternes et al, 1999;Baronti et al, 2000;Kolodziej et al, 2003;Yamamoto et al, 2006;Chen et al, 2010;Chang et al, 2011;Fan et al, 2011). Quantifying five classes of steroid hormones in the surface waters of Beijing (China) revealed that androgens (up to 1.9 μg l − 1 ) were the most abundant steroids in urban rivers (Chang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In particular APPI was shown to be able to detect steroid hormones down to several ng/L and had been proven to have much higher sensitivity than ESI. (Yamamoto et al, 2006;Viglino et al, 2008). Atmospheric pressure photoionization is the ionization of choice for PAHs and showed results comparable to gas chromatography mass spectrometry (Itoh et al, 2006;Cai et al, 2009).…”
Section: Ionization Techniquesmentioning
confidence: 95%
“…suggested that APPI could be considered as a more universal ionization method since APPI was able to ionized more compounds, with greater structural diversity, than ESI and APCI (Cai et al, 2005). Because of the capacity of APPI to ionize compounds with various polarities, it has been successfully applied frequently to environmental and pharmaceutical samples (Cai et al, 2005;Yamamoto et al, 2006;Viglino et al, 2008;Garcia-Ac et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation